(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2015)
Introduction: Anthropometry is applied to obtain measurements of living subjects for identifying age, stature, proportions body and/ or face and various dimensions related to particular race or an individual. Facial anthropometric studies have got vast implications in health related fields and are useful for orthodontists, plastic surgeons, maxillofacial surgeons for their treatment plans to evaluate treatment prognosis and determine treatment outcome. Prior to advent of cephalometric radiography, orthodontists often used anthropometric measurements to establish facial proportion. Although for orthodontists, this method was largely replaced by cephalometric analysis for many years, the recent emphasis on soft tissue proportions has brought soft tissue evaluation back into prominence. When there are questions about vertical facial proportions, it is better to make the measurement clinically rather than cephalometric analysis, because the soft tissue proportions, as seen clinically determine the facial appearance. Objective: To evaluate morphological facial height and to establish the upper & lower facial height proportions in Bangladeshi adult and to compare with similar data of various nations & ethnic groups. Method: This study was a descriptive observational cross sectional study by convenient sampling, conducted in AFMI (Armed Forces Medical Institute) among the 500 participants of Bangladeshi by birth with equal sex distribution aged 18-25 years. The anthropometric landmarks the nasion(n), subnasale (sn) and ganthion (gn), were marked on the participants face with a dermographic pen. With the help of a digital vernier sliding calipers, the measurements were taken in millimeters and the participant was in centric relation when measuring the facial height. The distance from n to sn is upper facial height (UFH), from sn to gn is lower facial height (LFH) and total facial height (TFH) is the sum of UFH and LFH. Conclusion: There is strong correlation among upper, lower and total facial height. The facial height proportion found in this study matches with ideal facial proportion widely practiced in clinical orthodontics for treatment planning and to determine treatment outcome. The findings of this study may help to establish the norms of facial proportion in Bangladeshi adult which will be helpful for treatment planning in orthodontic and reconstructive surgery without chephalomtric means. Journal of Armed Forces Medical College Bangladesh Vol.10(2) 2014